Of bulls and bulbs: aspirations, opinions and perceptions of rural adolescents and youth in Zambia. Issue 7 (3rd October 2019) - Daum, Thomas
ABSTRACT: In Africa, policymakers and development practitioners focus heavily on making farming more attractive for the youth. To reach this goal, different actions are proposed, often emphasising the need for modern technology. These proposed actions are mostly based on anecdotes and prior policy beliefs. Using interviews and drawing exercises, this article shows that the aspirations, opinions and perceptions of adolescents (pre-youth) and youth are more diverse than assumed by the prevailing orthodoxies. The findings suggest that policymakers and development practitioners should pay more attention to their views, comprising environmental and social concerns, to avoid misguided policies.